Dampak Kebijakan Hilirisasi CPO pada Industri Hilir Margarin terhadap Penerimaan Devisa Ekspor Indonesia - Asifa, Asifa; Hidayat, Nia Kurniawati; Novindra, Novindra (Ekonomis: Journal of Economics and Business, 2026)
Downstream programs in various fields have given birth to several policies, including policies in downstream Crude Palm Oil (CPO) which encourages an increase in foreign exchange or labor absorption. One of the downstream CPO products in high-value-added ceramics is margarine. The demand for margarine products has been increasing every year because margarine is used as a food ingredient. This study used dynamic simultaneous equations spanning the last 25 years (1998-2022) and was processed using SAS software. In this study, an analysis was carried out on what factors affect the demand for CPO by the downstream margarine industry, the demand and supply of domestic margarine products, and the export of Indonesian margarine products. This study also analyzes the impact of downstream policies on the margarine industry, including increasing the export tax on CPO as a raw material for margarine, increasing the production capacity of the downstream margarine industry, or a combination of the two policies. The research concluded that increasing the CPO export tax led to a decrease in CPO export volume, which led to an increase in CPO supply and CPO demand by the margarine downstream industry while increasing production capacity encouraged an increase in demand for CPO by the margarine industry and an increase in CPO prices, then affected in increasing in palm oil productivity. The combination of these two policies has a positive impact on increasing the downstream of CPO into marginal, but they need to be encouraged by the government in the future, therefore it can generate a higher export foreign exchange value.